Missed tubal ectopic pregnancy in hysterectomised patient: a rare case report - Satodiya, Mohit; Takkar, Navneet; Pandher, Dilpreet Kaur (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Tubal ectopic pregnancy (EP) in hysterectomised patient is uncommon. It has propensity to be overlooked. We report a rare case of missed tubal ectopic in 46 years old hysterectomised patient. She presented with abdominal pain and adnexal mass on imaging. Diagnosis was only possible intraoperatively owing to overlapping symptoms and imaging features with that of ovarian tumor.